DEVELOPMENT OF LKS BASED ON REALISTIC MATHEMATICS EDUCATION (RME) ON ONE VARIABLE LINEAR EQUALITY AND INEQUALITY - Rezky Putry Amelia; Sri Sutarni (Prima: Jurnal Pendidikan Matematika, 2023)
This study uses development research using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. This study aims to produce a teaching material product, namely the Realistic Mathematics Education (RME) Based Student Worksheet (LKS), feasible or valid and practical. This research has done at SMP Muhammadiyah 7 Bayat, Bayat, Kab. Klaten. The subjects of this study were experts, namely lecturers, teachers, and students of class VII SMP Muhammadiyah 7 Bayat, totaling ten people. The type of data used is in the form of quantitative and qualitative data. The data collection instrument used in this study was a questionnaire. Based on the validity test results, the Realistic Mathematics Education (RME) based Student Worksheet (LKS) stated in the very feasible or very valid category, with the percentage data from material experts being 87.5%. The results of the percentage data from teaching materials experts being 90.2% included in the very feasible or very valid category. Based on the results of the practicality test using a student response questionnaire based on the Realistic Mathematics Education (RME) Student Worksheet, this includes in the efficient category with a percentage result of 86.92%. The results show that the Realistic Mathematics Education (RME) based Student Worksheet (LKS) on the material of one-variable linear equations and the developed inequalities can employ in learning mathematics.